Sevoflurane inhibits progression of glioma via regulating the HMMR antisense RNA 1/microRNA-7/cyclin dependent kinase 4 axis. Issue 1 (1st January 2021) - Bao, Xi'an; Peng, Yibo; Shen, Jun; Yang, Longqiu
ABSTRACT: Sevoflurane (Sev) is a volatile anesthetic that can inhibit tumor malignancy. Glioma is a main brain problem, but the mechanism of Sev in glioma progression is largely unclear. This study aims to explore a potential regulatory network of long noncoding RNA (lncRNA)/microRNA (miRNA)/mRNA associated with the function of Sev in glioma progression. LncRNA HMMR antisense RNA 1 (HMMR-AS1), miR-7 and cyclin-dependent kinase 4 (CDK4) abundances were examined via quantitative reverse transcription polymerase chain reaction and western blot. Cell viability, invasion, and colony formation ability were analyzed via cell counting kit-8, transwell analysis, and colony formation. The target association was analyzed via dual-luciferase reporter analysis and RNA pull-down. The in vivo function of Sev was investigated by xenograft model. HMMR-AS1 abundance was increased in glioma tissues and cells, and reduced via Sev. Sev constrained cell viability, invasion, and colony formation ability via decreasing HMMR-AS1 in glioma cells. miR-7 expression was decreased in glioma, and was targeted via HMMR-AS1. HMMR-AS1 silence restrained cell viability, invasion, and colony formation ability by up-regulating miR-7 in glioma cells. Sev increases miR-7 abundance via decreasing HMMR-AS1. CDK4 was targeted via miR-7, and highly expressed in glioma. miR-7 overexpression inhibited cell viability, invasion, and colony formation ability via reducing CDK4 in glioma cells. CDK4 expression was reduced by Sev via HMMR-AS1/miR-7 axis. Sev suppressed cell growth in glioma by regulating HMMR-AS1. Sev represses glioma cell progression by regulating HMMR-AS1/miR-7/CDK4 axis.